Enhanced Depth-First Search Algorithm for Improving the Efficiency of Route Construction in Data Center Networks - Abbass, Ayam Mohsen; Ahmed Yousif Falih Saedi; Kadhim, Jaafar Qassim (Engineering, Technology & Applied Science Research, 2025)
Data transmission is a critical component of data center networks, ensuring efficient and reliable data transfer between nodes. Using the shortest path for data transmission is a common approach in data center networks, as it helps minim. Nevertheless, this methodology may also give rise to some challenges, including those related to network congestion and heightened susceptibility to node failures. In light of the inherent self-similarity and multipath routing characteristics shown by the Fat Tree topology, this work proposed a modified search method aimed to enhance the efficiency of the depth-first search (DFS) method. The comparison is made between the modified algorithm and the original algorithm operating on the conventional network architecture seen in data centers. The findings highlight the distinctive advantages of the modified DFS method, demonstrating its enhanced scalability and effectiveness in minimizing latency. The modified DFS technique consistently excels in reducing energy usage under various network load circumstances.